Le colpe dei padri. Commento all’ordinanza della Corte di Cassazione n. 8325 del 29 aprile 2020 (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Introduzione - 2. La genitorialità intenzionale nell’attuale giurisprudenza italiana - 3. Profili critici - 4. La questione di illegittimità costituzionale - 5. Scenari possibili.The Sins of the Fathers. Comment to Corte di Cassazione, judg. n. 8325 April 29th 2020.ABSTRACT: This essay examines the Italian judgement (Ordinanza) n. 8325, issued on April 2020, that has raised a question of constitutionality against the jurisprudential address which, appealing to the limit of the public order, excludes the Italian recognition of foreign jurisdictional decisions that ascertain the right to be inserted - as an intentional parent - in the birth certificate of a child born through the so-called “surrogate motherhood”. In particular, after a survey of the current Italian case law (§ 2) and the problems that it raises (§ 3), the essay examines the arguments advanced by the judgement (§ 4), wondering about its possible outcomes (§ 5).